COMBINE: Leveraging the Power of Wireless Peers through Collaborative Downloading - Ananthanarayanan, Ganesh; Padmanabhan, Venkat; Ravindranath, Lenin; Thekkath, Chandu (ACM MobiSys, 2007)
Mobile devices are increasingly equipped with multiple network interfaces: Wireless Local Area Network (WLAN) interfaces for local connectivity and Wireless Wide Area Network (WWAN) interfaces for wide-area connectivity. The WWAN typically provides much wider coverage but much lower speeds than the WLAN. To address this dichotomy, we present COMBINE, a system for collaborative downloading wherein devices that are within WLAN range pool together their WWAN links, signiﬁcantly increasing the eﬀective speed available to them. COMBINE makes a number of novel contributions over prior work in this area, including: (a) a framework of incentives for collaboration that addresses several practical issues including the uniﬁcation of monetary and energy costs, and on-the-ﬂy estimation of the energy cost of communication in a system in operation; (b) a protocol for collaborative group formation and workload distribution that is energy eﬃcient and adaptive to ﬂuctuations in network conditions; and (c) an application-level striping procedure that eases deployment by avoiding the need for special-purpose proxies in the infrastructure. We present experimental results based on the prototype we have implemented that show encouraging speeds-ups with COMBINE.